Hubungan Keberadaan Runtunan Ofiolit dengan Konsentrasi Unsur Logam dalam Endapan Sungai Aktif di Daerah Pelaihari, Kalimantan Selatan - Baharuddin Baharuddin (Pusat Survei Geologi, 2006)
Pelaihari and its surrounding area which belong to the Tambak-Tamban- Bobaris Zone are part of the western limb of the Meratus High. The area has significant metalliferous mineral prospects. Geologically, the area is occupied by ultramafic, intrusive, volcanic, sedimentary, and metamorphic rocks with ages range from Mesozoic to Tertiary. The results of geochemical analyses of active stream sediment samples in this area indicate a close relationship between the distribution of the rocks and concentration of metallogenic elements within the stream sediment samples. Concentration of nickel (Ni) and copper (Cu) elements increase within the stream sediment in the northeastern area while platinum (Pt) and cobalt (Co)show a significant high concentration value in the southern area except Co which also has a high concentration value in central and northeastern area. This high metallogenic concentration presumably derived from the existence of ophiolite sequence in this area.Â Keywords: Ophiolite sequence, active stream sediment, concentration of metallogenic elements